A MICROBIAL CONTAMINATION OF PROSTATIC TISSUE IN BENIGN PROSTATIC HYPERPLASIA AND PROSTATE CANCER - Y. L. Naboka; M. B. Chibichyan; A. V. Ilyash (Вестник урологии, 2013)
Bacteriological results of prostatic tissue in benign prostatic hyperplasia and prostate cancer are shown in this article. A use of extended amount of media for bacterial isolation allows a wide spectrum of nonclostridial anaerobic (Bacteroides sp., Bifidobacterium sp., Eubacterium sp., Propionibacterium sp., Рeptococcus sp., Peptostreptococcus sp., Prevotella sp., Veilonella sp., Fusobacterium sp., Streptococcus sp., Capnocytophaga ochracea) and aerobic bacteria (Corynebacterium sp., Enterococcus sp., E. coli, S. haemolyticus, S. hominis). It is revealed that nonclostridial anaerobes are predominant flora in qualitative and quantitative terms in prostate cancer as well as benign prostatic hyperplasia. Both a mean level of bacterial contamination of prostate bioptates and incidence rate of most bacteria was higher in patients with benign prostatic hyperplasia.